Unveiling Local Power Through Microhistory: A Multidisciplinary Analysis of Early Modern Husbandry Practices in Casaio and Lardeira (Ourense, Spain) - Tejerizo-García Carlos (Open Archaeology, 2024)
Following the proposal for the special issue, the aim of this study is to reflect on the potentialities and setbacks of a micro-historical approach to the archaeological record. This will be done by analysing the local organization of Early Modern husbandry in a territory in northwestern Iberia, where investigations have been carried out since 2017. I will apply the theoretical background of microhistory to four specific archaeological sites to delve into the social structuring and power relationships among the different agents involved in stockbreeding in the territory. In this regard, I will argue that one of the most compelling contributions of microhistory is to delve into the deep connection between the systemic and the quotidian, between structure and agency. However, this connection is not always straightforward and visible in the sources, and thus a deep theoretical and methodological background becomes necessary to understand questions such as how power was conceived and articulated at the local level and in daily life.